Six-Minute Walk Distance After Critical Illness: A Systematic Review and Meta-Analysis. (March 2021) - Parry, Selina M.; Nalamalapu, Swaroopa R.; Nunna, Krishidhar; Rabiee, Anahita; Friedman, Lisa Aronson; Colantuoni, Elizabeth; Needham, Dale M.; Dinglas, Victor D.
Background and Objectives: Impaired physical functioning is common and long lasting after an intensive care unit (ICU) admission. The 6-minute walk test (6MWT) is a validated and widely used test of functional capacity. This systematic review synthesizes existing data in order to: (1) evaluate 6-minute walk distance (6MWD) in meters over longitudinal follow-up after critical illness, (2) compare 6MWD between acute respiratory distress syndrome (ARDS) versus non-ARDS survivors, and (3) evaluate patient- and ICU-related factors associated with 6MWD. Data Sources: Five databases (PubMed, EMBASE, Cumulative Index of Nursing and Allied Health Literature, PsychINFO, and Cochrane Controlled Trials Registry) were searched to identify studies reporting 6MWT after hospital discharge in survivors from general (ie, nonspeciality) ICUs. The last search was run on February 14, 2018. Databases were accessed via Johns Hopkins University Library. Data Extraction and Synthesis: Pooled mean 6MWD were reported, with separate linear random effects models used to evaluate associations of 6MWD with ARDS status, and patient- and ICU-related variables. Twenty-six eligible articles on 16 unique participant groups were included. The pooled mean (95% confidence interval [CI]) 6MWD results at 3- and 12-months post discharge were 361 (321-401) and 436 (391-481) meters, respectively. There was a significant increase in 6MWD at 12 months compared to 3 months ( P = .017). In ARDS versus non-ARDS survivors, the mean (95% CI) 6MWD difference over 3-, 6-, and 12-month follow-up was 73 [13-133] meters lower. Female sex and preexisting comorbidity also were significantly associated with lower 6MWD, with ICU-related variables having no consistent associations. Conclusions: Compared to initial assessment at 3 months, significant improvement in 6MWD was reported at 12 months. Female sex, preexisting comorbidity, and ARDS (vs non-ARDS) were associated with lower 6MWT results. Such factors warrant consideration in the design of clinical research studies and in the interpretation of patient status using the 6MWT.